MICRO-54: 54th Annual IEEE/ACM International Symposium on Microarchitecture 2021
DOI: 10.1145/3466752.3480059
|View full text |Cite
|
Sign up to set email alerts
|

ADAPT: Mitigating Idling Errors in Qubits via Adaptive Dynamical Decoupling

Abstract: The fidelity of applications on near-term quantum computers is limited by hardware errors. In addition to errors that occur during gate and measurement operations, a qubit is susceptible to idling errors, which occur when the qubit is idle and not actively undergoing any operations. To mitigate idling errors, prior works in the quantum devices community have proposed Dynamical Decoupling (DD), that reduces stray noise on idle qubits by continuously executing a specific sequence of single-qubit operations that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Both papers evaluate DD sequences on simple benchmarks instead of real quantum applications, and there is no experiment to illustrate applying KDD to IBM quantum devices. Moreover, the experiments in [15] show that the naive implementation of DD (inserting DD sequences to all the idle qubits when it is possible) can not always improve the circuit fidelity. Therefore, Das et al proposed an Adaptive Dynamical Decoupling framework to estimate the DD impact for each circuit and adjust DD sequence to ensure it improves the circuit fidelity [15].…”
Section: A Dynamical Decouplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Both papers evaluate DD sequences on simple benchmarks instead of real quantum applications, and there is no experiment to illustrate applying KDD to IBM quantum devices. Moreover, the experiments in [15] show that the naive implementation of DD (inserting DD sequences to all the idle qubits when it is possible) can not always improve the circuit fidelity. Therefore, Das et al proposed an Adaptive Dynamical Decoupling framework to estimate the DD impact for each circuit and adjust DD sequence to ensure it improves the circuit fidelity [15].…”
Section: A Dynamical Decouplingmentioning
confidence: 99%
“…Moreover, the experiments in [15] show that the naive implementation of DD (inserting DD sequences to all the idle qubits when it is possible) can not always improve the circuit fidelity. Therefore, Das et al proposed an Adaptive Dynamical Decoupling framework to estimate the DD impact for each circuit and adjust DD sequence to ensure it improves the circuit fidelity [15]. This method achieves fidelity improvement but introduces a large overhead of DD impact characterization for a given application.…”
Section: A Dynamical Decouplingmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) What conditions lead to idle qubits and what is the strategy to insert DD to idle qubits under different conditions? The first question was discussed in [17], where the authors comprehensively evaluated the performance [5]. They demonstrated that DD performs better when applied to a subset of qubits rather than all.…”
Section: Related Workmentioning
confidence: 99%
“…Several quantum software tools were developed to help design DD insertion strategies to obtain better circuit fidelity. Das et al proposed ADAPT [5], an adaptive DD framework to insert DD pulses to a subset of idle qubits. Moreover, Ravi et al introduced VAQEM [20], which dynamically selects the length of DD sequence for variational quantum algorithms.…”
Section: Introductionmentioning
confidence: 99%